Insights Into Parkin-Mediated Mitophagy in Alzheimer's Disease: A Systematic Review - Goudarzi, Sepideh; Hosseini, Asieh; Abdollahi, Mohammad; Haghi-Aminjan, Hamed (Frontiers in Aging Neuroscience, 2021)
Background: Parkin-mediated mitophagy is the dominant mitophagy pathway of neural cells. Its restoration will result in prevention of cognitive decline, including Alzheimer's disease (AD). The role of this mitophagy pathway in neurodegenerative diseases has drawn attention in recent years. The two main pathological proteins in AD, amyloid β (Aβ) and human Tau (hTau), interfere with mitochondrial dynamics through several pathways. However, taking into consideration the specific interactions between Aβ/hTau and Parkin, special focus is required on this mitophagy pathway and AD. In this review, these interactions are fully discussed, and an overview of the neuroprotective drugs that enhance Parkin-mediated mitophagy is presented. Methods: This systematic review was performed according to PRISMA guidelines, and a comprehensive literature search was done in the electronic databases up to September 2020, using search terms in the titles and abstracts to identify relevant studies. One hundred eighty-six articles were found, and 113 articles were screened by title and abstract. Finally, 25 articles were included in this systematic review according to our inclusion and exclusion criteria. Results: Accumulation of Aβ and hTau affects mitophagy, including Parkin-mediated. Tau seems to prevent Parkin translocation directly. A Parkin level in the cell appears to be of importance in determining the damage caused by Aβ and hTau and in the future therapeutic approaches. Parkin controls the PINK1 level via the presenillins, suggesting that mutations in presenillins affect Parkin mitophagy. Significance: Parkin mitophagy is a process affected by several AD pathological events multidimensionally.